KELAYAKAN TEORETIS PERMAINAN TIGER BIOLOGY SEBAGAI MEDIA PEMBELAJARAN KELAS VII PADA MATERI PENCEMARAN LINGKUNGAN - JAYA WIKRAMA MEDP, PAMUJI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Traditional game that consistently follow the development of period which going modern is combine traditional aspect in technology, there is tiger biology game using computer program application. The research was conducted to produce tiger biology game as learning media in environment pollution matter and to describe the theoretical and empirical feasibility. The development of tiger biology game using visual basic windows. This media design research using ASSURE method. The research result showed that tiger biology game worthy theoretically feasibility based on the validation from media in aspect of media format, language and design of media got value about 95,13% and got score in very feasibility category. Keywords: media, pollution, tiger biology, theoretical feasibility